1991
DOI: 10.3171/jns.1991.74.1.0014
|View full text |Cite
|
Sign up to set email alerts
|

Risks factors for cerebral infarction in good-grade patients after aneurysmal subarachnoid hemorrhage and surgery: a prospective study

Abstract: A prospective series of 265 patients with aneurysmal subarachnoid hemorrhage (SAH) of Grades I to III (Hunt and Hess classification) upon admission were evaluated as to neurological outcome and computerized tomography (CT) findings 1 to 3 years (mean 1.4 years) after the SAH and surgery. A total of 73 patients underwent acute surgery (within 72 hours after the bleed: Days 0 to 3), 86 were operated on subacutely (between Days 4 and 7), and 91 had late surgery (on Day 8 or later). Fifteen patients died before su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 37 publications
2
60
1
2
Order By: Relevance
“…The timing of surgery is not associated with the outcome or have a relatively small influence on the outcome (14,20,29). There was no significant difference between incidences of cerebral infarcts in patients who underwent emergent surgery (22).…”
Section: Operation Stagementioning
confidence: 98%
See 2 more Smart Citations
“…The timing of surgery is not associated with the outcome or have a relatively small influence on the outcome (14,20,29). There was no significant difference between incidences of cerebral infarcts in patients who underwent emergent surgery (22).…”
Section: Operation Stagementioning
confidence: 98%
“…Disney et al (7) reported that initial systolic blood pressure had relative importance as a prognostic factor in outcomes, although other authors claim that a history of essential arterial hypertension is not related to outcome (11,14,20). In the study by Ohman et al (22) a history of hypertension was reported to be a prognostic factor for cerebral infarction in patients after aneurysmal SAH.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, treatment with nimodipine and hemodynamic maneuvers may have decreased the risk of delayed cerebral ischemia. Despite widespread opinion to the contrary, nimodipine may reduce angiographic vasospasm 40,41 and cerebral infarction. 44,47 The increasing use of endovascular treatment of aneurysms and the decreasing use of invasive arteriography in favor of less invasive alternatives (CT or magnetic resonance angiography) may also alter the incidence and severity of angiographic vasospasm after SAH.…”
Section: Does Sah Cause Vasospasm?mentioning
confidence: 99%
“…The criteria to consider patients as high risk for CVS included severity of clinical findings (WFNS [17] grades 3-5, Hunt and Hess [18] grades II -V) [19][20][21], volume of blood in the cisterns and ventricles (Fisher grades 3 and 4) [22], signs of rebleeding prior to treatment [23], young age [24], nicotine consumption [25], cocaine abuse [26,27], hypertension [28,29], and hyperglycemia [29]. Gender was not considered as risk factor for CVS in this study [30].…”
Section: Patient Population and Treatment Protocolmentioning
confidence: 99%